ESTIMASI KANDUNGAN KARBON PADA BERBAGAI TINGKAT KERAPATAN VEGETASI DI LAHAN GAMBUT KECAMATAN ALUH-ALUH - Tenti Linda Lestari; Wahyuni Ilham; Mufidah Asy'ari (Jurnal Sylva Scienteae, 2020)
Aluh Aluh is one sub-district in the Banjar Regency, South Kalimantan province with 82.48 km2 wide and most of the districts, the peat distribution is quite extensive and unprecedented land fires. Peat is one of the largest carbon sequester beneath the surface (in the ground). The measurement of carbon sequestration in soils need to be done in order to configure certain amount (value) of carbon stored in the peat. The purpose of this research is to estimate the potential of the carbon stored in various levels of land vegetation density in peatland, based on NDVI value Aluh-Aluh district. The research was carried out with the analysis of NDVI and Equal Intervals classification method to divide the class vegetation density, followed by sampling the soil for Bulk Density and C-organic analysis. The results of this study showed that the NDVI value ranges between 0.3 – 0.48 included in the rare vegetation density, the value of 0.48 0.66 – included in the medium vegetation density, whereas the value 0.66 0.85 – included in the high vegetation density. Based on the soil carbon content, the three levels of the vegetation density have the different potential of carbon stored. The potential of the carbon stored in rare vegetation density amounted to 43,240.01 tons/ha of land from an area of 3,233.14 ha, on the medium vegetation density the potential carbon stored valued 11,513.08 tons/ha of land area 1,242.91 ha and on the high vegetation density has 6,939.85 tons/ha potential stored carbon from 677.91 ha peat area.Keywords: Peatlands; soil carbon; NDVI; Bulk Densit; C-organic